Continuous‐Wave Pumped Perovskite Lasers. Issue 17 (3rd June 2019) - Mi, Yang; Zhong, Yangguang; Zhang, Qing; Liu, Xinfeng
Abstract: Continuous‐wave (CW) operated lasers are regarded as a stepping stone to the development of electrically driven lasers and crucial for practical application in high‐density integrated optoelectronic devices. Recently, metallic halide perovskites are demonstrated as excellent gain materials for CW lasers owing to their large optical absorption coefficient, low defect density, long diffusion length, and suppressed Auger recombination rate. Here, the latest research advances on CW pumped perovskite lasers are reviewed. First, the recent research advances on CW lasing in perovskite thin film are highlighted. Then, CW lasing in CsPbBr3 perovskite nanowires is briefly introduced. The comparison of lasing thresholds in CW perovskite lasers is made and discussed. Finally, the importance of such perovskite CW lasers is emphasized, while a perspective on the potential opportunities and remaining challenges of perovskite‐based CW lasers is proposed. Abstract : Continuous‐wave (CW) lasers are crucial for practical application in high‐density integrated optoelectronic devices . Herein, the latest research advances on CW perovskite lasers of thin film and nanowires are reviewed. The comparison of thresholds in CW perovskite lasers is discussed, and the significance of CW perovskite lasers is emphasized, while a perspective of potential opportunities and remaining challenges is proposed.